Lean applied to logistics: a case study - Lourenço, Leonel (2015)
This project aims to study the implementation of Lean principles and tools in several levels of logistics, from internal logistics to interface with distribution center and suppliers, in an industrial plant. The main focus of all efforts is to create the conditions to approach the continuous flow scenario in the manufacturing processes. The subject of improvement actions is a company whose core activity is car seat production, more specifically the car seat cover production and assembly. This focuses the assembly process, which requires the usage of a considerable variety of components and therefore is an important obstacle to the implementation of continuous flow. The most salient issues are related with inefficient interaction between sections and late supply of components in assembly lines, forcing the operator to abandon his work station and leading to production interruption. As an operational methodology, actions from Lean philosophy and optimization were implemented according to project management principles.